Spatially Confined UHF RFID Detection With a Metamaterial Grid - Morgado, T.; Alves, J. M.; Marcos, J.; Maslovski, S.; Costa, J. R.; Fernandes, C. A; Silveirinha, M. G. (IEEE Transactions on Antennas and Propagation, 2014)
The confinement of the detection region is one of the most challenging issues inUltra-High Frequency (UHF) Radio Frequency Identification (RFID) systems.Here, we propose a new paradigm to confine the interrogation zone of standard UHF RFID systems. Our approach relies on the use of an all-planar metamaterial wire grid to block the radiation field (i.e., the far-field) of the reader antenna, and thereby obtain a spatially well-confined detection region in the near-field. This solution is analytically and numerically investigated, and then experimentally verified through near-field and tag-reading measurements, demonstrating its effectiveness and robustness under external perturbations.